2017
DOI: 10.4209/aaqr.2016.09.0422
|View full text |Cite
|
Sign up to set email alerts
|

Regional Impact of Biomass Burning in Southeast Asia on Atmospheric Aerosols during the 2013 Seven South-East Asian Studies Project

Abstract: A nested air quality prediction modeling system (NAQPMS) with an online tracer-tagged module was utilized to investigate the regional impact of biomass burning (BB) on aerosols and source-receptor relationships in Southeast Asia during March-April 2013. NAQPMS could reproduce the three-dimensional spatial distribution of aerosols. Both monthly and episodic analyses indicated that BB significantly contributed to surface and column aerosol concentrations in Southeast Asia along two long-range transport pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Several studies have used a mix of models and observations to explore the impacts of fire on atmospheric aerosol properties, visibility, and/or air quality in Mainland Southeast Asia (Duc et al., 2016; K. Huang et al., 2013; Lee et al., 2017, 2018; Li et al., 2017; Lin et al., 2013; Vongruang & Pimonsree, 2020; Yin et al., 2019). However, studies quantifying the contribution of fire to particulate air pollution, population exposure and public health are lacking in this region (H. J. Johnston et al., 2019; Yadav et al., 2017), compared in particular to the large number of studies focused on Equatorial Asia (e.g., Crippa et al., 2016; Kiely et al., 2020; Koplitz et al., 2016; Marlier et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have used a mix of models and observations to explore the impacts of fire on atmospheric aerosol properties, visibility, and/or air quality in Mainland Southeast Asia (Duc et al., 2016; K. Huang et al., 2013; Lee et al., 2017, 2018; Li et al., 2017; Lin et al., 2013; Vongruang & Pimonsree, 2020; Yin et al., 2019). However, studies quantifying the contribution of fire to particulate air pollution, population exposure and public health are lacking in this region (H. J. Johnston et al., 2019; Yadav et al., 2017), compared in particular to the large number of studies focused on Equatorial Asia (e.g., Crippa et al., 2016; Kiely et al., 2020; Koplitz et al., 2016; Marlier et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies quantifying the contribution of fire to particulate air pollution, population exposure and public health are lacking in this region (H. J. Johnston et al., 2019; Yadav et al., 2017), compared in particular to the large number of studies focused on Equatorial Asia (e.g., Crippa et al., 2016; Kiely et al., 2020; Koplitz et al., 2016; Marlier et al., 2012). Recent studies show that fire is the dominant cause of the variation of local ambient air quality in Mainland Southeast Asia (Yin et al., 2019); contributing 49% of ambient PM 10 (particulate matter with aerodynamic diameter ≤ 10 μm) concentrations during peak open burning in March 2012 (Vongruang & Pimonsree, 2020) and 70%–80% to aerosol optical depth in source regions during March‐April 2013 (Li et al., 2017). Preventing fire could yield substantial reductions in population‐weighted PM 2.5 (particulate matter with aerodynamic diameter ≤ 2.5 μm) concentrations across Mainland Southeast Asia (Reddington, Conibear, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The BB contributions to PM 10 concentrations of the four simulation cases were 2%-12% at Bangkok and 75%-89% at Chiang Mai for each day that the maximum concentrations were observed. Li et al [12] reported that BB contributions to simulated PM 2.5 was 70%-80% in the BB source regions during March-April 2013 and the contributions were close to 75%-89% at Chiang Mai on 21 March 2014. Figure 6 shows simulated and observed wind speed, planetary boundary layer (PBL) height, and daily concentrations at Bangkok and Chiang Mai from March to April.…”
Section: Daily Concentrations Of Pm 10 At Observation Sitesmentioning
confidence: 97%
“…However, particulate matter was not evaluated in the simulations. Li et al [12] reported that BB contributed 70%-80% of simulated PM 2.5 in northern Myanmar, Laos, and Vietnam during March-April 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass burning emission causes a significant perturbation to global atmospheric chemistry (Stocks et al, 2000;Akagi et al, 2011;Grell et al, 2011;Lin et al, 2017;Popovicheva et al, 2017;Pani et al, 2018;Liang et al, 2019). It has an impact of direct and indirect effects on the radiative forcing of atmospheric aerosol particles and climate change (Li et al, 2017;Martins et al, 2018;Bukowiecki et al, 2019;Huang et al, 2019). Chemical compounds in aerosol particles are used as tracers to determine the sources such as biomass burning emission (Decesari et al, 2006;Wang et al, 2009;Lee et al, 2016;Du et al, 2017;Cui et al, 2018;Popovicheva et al, 2019;Priyadharshini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%